Ethics of disagreement and its impacts on Muslim unity and IFTA - Islam, Tazul; Amanullah, Muhammad (Hamdard Foundation Press, Pakistan, 2013)
Disagreement is a common phenomenon in human opinion because the level of thinking, the way of thinking, the realization of denotation of the Scriptures and their context may not be equal. If disagreement is operated within a sound framework and its ethical boundary, it could enrich the Muslim mind, stimulate intellectual development, expand perspectives and make them look at problems and issues in their wider and deeper ramifications. Whereas, if it is devoid of ethical and methodological standards, the result will definitely be inauspicious, such as outbreak of mutual jealousy, religious schism and internal disintegration which directly contribute to create a vast chasm and disunity within the Ummah. Following analytical and critical methods, this paper presents some important principles of ethics of disagreement, undertakes a historical survey of the impacts of disagreement on Muslim Unity, highlights on blind imitation and dogmatism from Islamic ethical viewpoint and discusses the negative impacts of disagreement on Ifta’.